The Effect of Lower Body Compression Tights on the Running-Based Anaerobic Sprint Test in Young Male Basketball Players - Mustafa Can Üster; Cem Kurt; İlbilge Özsu Nebioğlu (Pamukkale University, 2024)
This study aims to assess the influence of lower body compression tights on performance in the Running-Based Anaerobic Sprint Test (RAST) in young male basketball players. Twenty male basketball players participated in the study (age = 16.5±0.5 years, height = 176.8±5.71 cm, weight = 68.5±8.98 kg, basketball experience = 2.35±0.49 years). Players performed the RAST, comprising 6 x 35 m sprints with 10-second intervals, wearing regular shorts or compression tights, with a one-week interval between conditions. Before each test, a 24-hour dietary record was used to calculate the total calorie intake and the percentage of calories from carbohydrates to account for dietary variations. The Hooper Index was used to assess fatigue levels before each test. The RAST, conducted using a Newtest Powertimer photocell (300 Series, Oulu, Finland), determined maximal power (Pmax), minimum power (Pmin), average power (AP), and fatigue index (FI). Perceived exertion after each RAST was assessed using the Borg Scale (20-point system). Paired-samples ttest results showed no statistically significant difference (p>0.05) between the means from the two test sessions. The study suggests that lower body compression tights did not significantly impact RAST performance in young basketball players. Considering the study design, applying it to more experienced players after familiarization sessions with compression tights may yield different results.